The Goldilocks Quandary of Health Care Resources: Too Little, Too Much, or Just Right?. Issue 6 (June 2016) - Morgan, Daniel M.; Main, Elliott; Gee, Rebekah E.
Abstract : Appropriate use of health care resources is a priority for improving the quality of care. Overutilization affects almost all specialties including obstetrics and gynecology. Initiatives such as the Choosing Wisely campaign and the Joint Commission Perinatal Care Measures have brought attention to issues of overuse. The decision of these campaigns to focus on eliminating nonmedically indicated inductions before 39 weeks of gestation is an example of how more appropriate health care use can reduce complications and save millions of dollars. Cesarean delivery, hysterectomy, and prophylactic oophorectomy are procedures with high levels of variation in utilization, and the use of an intrauterine device is an example of underutilization. Efforts to promote adherence to best practices such as those directed at nonmedically indicated inductions could lead to more appropriate use of these interventions and improve women's health care. Abstract : There is an increased national focus on the overuse and underuse of common obstetric and gynecologic procedures or treatments.